2017
DOI: 10.1016/j.molp.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Exchange and Regulation in Arbuscular Mycorrhizal Symbiosis

Abstract: Most land plants form symbiotic associations with arbuscular mycorrhizal (AM) fungi. These are the most common and widespread terrestrial plant symbioses, which have a global impact on plant mineral nutrition. The establishment of AM symbiosis involves recognition of the two partners and bidirectional transport of different mineral and carbon nutrients through the symbiotic interfaces within the host root cells. Intriguingly, recent discoveries have highlighted that lipids are transferred from the plant host t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
237
2
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(279 citation statements)
references
References 140 publications
2
237
2
16
Order By: Relevance
“…Recently it has been shown that fatty acids are transported from the host to the fungus, likely serving as a major nutritive carbon source Keymer et al, 2017;Luginbuehl et al, 2017). However, previously it has been shown that the host also provides sugars as carbon source, although the mechanism by which sugars are transported to the fungus is unclear (Rich et al, 2017;Roth & Paszkowski, 2017;Wang et al, 2017). Therefore, in this study we investigated the role of SWEET sugar transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that fatty acids are transported from the host to the fungus, likely serving as a major nutritive carbon source Keymer et al, 2017;Luginbuehl et al, 2017). However, previously it has been shown that the host also provides sugars as carbon source, although the mechanism by which sugars are transported to the fungus is unclear (Rich et al, 2017;Roth & Paszkowski, 2017;Wang et al, 2017). Therefore, in this study we investigated the role of SWEET sugar transporters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been proposed previously that the plant sugar transporters should be regulated in response to the plant's intracellular phosphate level (Schott et al ., ). Indeed, different experimental evidence points to diverse nutrient status‐dependent regulation cascades (Roth & Paszkowski, ; Wang et al ., ). Our analyses indicate that the release of C sources in an electroneutral manner, albeit not optimal in terms of energetics and C use efficiency, could be beneficial in terms of P acquisition. Interestingly, SWEETs involved in the export of sugars, and homologs of adenosine triphosphate‐binding cassette (ABC) transporters, putatively involved in the export of fatty acids, have been found to be essential for, or upregulated during, arbuscule formation (Zhang et al ., ; Gutjahr et al ., ; Manck‐Götzenberger & Requena, ).…”
Section: Discussionmentioning
confidence: 97%
“…Our approach concludes with a transporter network (Fig. ) which is not in conflict with those that were sketched according to experimentally verified transporter expression data (Parniske, ; Bonfante & Genre, ; Smith & Smith, ; Behie & Bidochka, ; Wang et al ., ; Chen et al ., ). This fact validates our assumption and, moreover, our approach sheds light on the question marks that were still assigned to several transport pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a field split‐plot experiment, N‐deficient plots were strongly colonized by AM fungi when compared with N efficiency plants, despite high soil and tissue P concentrations ( Blanke et al., ). This may indicate that both P and N regulate this symbiosis and are delivered to the host through this plant‐fungus interaction ( Wang et al., ). The availability of essential soil resources, e.g ., soil N : P ratio, was an important force in the formation of geographic mosaics of symbiotic function in mycorrhizae; including N : P ratio of soil availability, and the AM fungi increased the uptake of the nutrient that was most limiting in the soil ( Johnson et al., ).…”
Section: Introductionmentioning
confidence: 99%